Comments by the Executive Director of SADF - Paulo Casaca (European Regional Science Association (ERSA), 2015)
The success of Mr Modi?s government is much more than a domestic issue; it is a fundamental challenge for democracy. India is not only the biggest democracy in the World; India is the only significant example of a XXth century born nation that never knew any other form of government. Nothing is settled regarding democracy in our age. One thing is however considerably safe to predict: the future of democracy is highly dependent on the success of the largest and most consistent emerging democracy. Modi?s election broke three enduring democracy hexes: thirty years without clear parliamentary majority; politics polarised by factional issues and dynastic entrenchment. It did so giving hope to hundreds of millions of people on consistent steps for development. And this is the crux of the matter for looking into this first year of Modi in government.
Keywords: 330